2020
DOI: 10.1109/tbme.2019.2962239
|View full text |Cite
|
Sign up to set email alerts
|

Disposable Paper-on-CMOS Platform for Real-Time Simultaneous Detection of Metabolites

Abstract: Objective: Early stage diagnosis of sepsis without overburdening health services is essential to improving patient outcomes. Methods: A fast and simple-to-use platform that combines an integrated circuit with paper microfluidics for simultaneous detection of multiple-metabolites appropriate for diagnostics was presented. Paper based sensors are a primary candidate for widespread deployment of diagnostic or test devices. However, the majority of devices today use a simple paper strip to detect a single marker u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Hu et al adapted an existing concept, a disposable paper system as is used in the rapid evaluation of blood glucose levels in patients with diabetes mellitus, to evaluate blood lactate levels; however, the limits of detection were relatively higher than biomarker studies. 34 Nevertheless, the concept is excellent and the disposable paper system has proven utility in the management of diabetes, indicating that it could be easily translatable as a bedside screening measure in emergency departments for the early recognition of sepsis. Additional screening could be completed on an as-needed basis per admitted patients' condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al adapted an existing concept, a disposable paper system as is used in the rapid evaluation of blood glucose levels in patients with diabetes mellitus, to evaluate blood lactate levels; however, the limits of detection were relatively higher than biomarker studies. 34 Nevertheless, the concept is excellent and the disposable paper system has proven utility in the management of diabetes, indicating that it could be easily translatable as a bedside screening measure in emergency departments for the early recognition of sepsis. Additional screening could be completed on an as-needed basis per admitted patients' condition.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Hu et al developed a disposable paper system similar to that used in glucose monitors for measuring the conversion of lactate and glucose to their oxidized form. 34 Their device utilized a sensor that measured light emitting diode light absorption after passing through the sample. The chromatography paper contained three channels for independent evaluation of lactate and glucose as well as a control that contained glutamate.…”
Section: Devices For Markers Of Perfusionmentioning
confidence: 99%
“…18,19 In recent years, complementary metal oxide semiconductor (CMOS) technology was introduced into various strip tests. [20][21][22] Oyaert et al conducted a series of studies on automatic dry chemical analysis (on a Sysmex UC-3500 urinary test strip reader) in combination with CMOS technology. Their results showed that the results of LE strips were quantifiable and could be mutually verified with leukocyte counts, which offered a feasible way to achieve quantitative detection of LE strips.…”
Section: Exploration Of Quantitative Detection Of Le Stripsmentioning
confidence: 99%
“…The size of the chip was 3.4 mm x 3.6 mm. The CMOS chip has been fully characterized in previous works [28]- [31]. The chip required wire bonding for use.…”
Section: Design and Simulationsmentioning
confidence: 99%